Broader horizons for animal personality research - Koski, Sonja E. (Frontiers in Ecology and Evolution, 2014)
Personality is at the forefront of current behavioral ecological research. Most research concerns boldness, aggressiveness, activity, exploratory tendency, and sociability. However, many species may exhibit consistent variation in other traits, which the current research problematically misses. Exclusive adherence to the five traits ignores the possibility that other traits may be more consequential for a species and limits our understanding of the personality trait repertoire and the potentially complex associations among the usually sampled and other traits. Selecting personality traits based on species' ecology is crucial for understanding the causes and consequences of personality, and assessing a broader range of personality traits yields a better understanding of the trait associations. Studying the five traits has been useful in delineating research methods and aims, but it is time to broaden the personality horizon.